Tata Kelola Sistem Informasi pada Perusahaan Pelayaran Lepas Pantai - Bimo Andono; Arif Imam Suroso; Ninuk Purnaningsih (School of Business, Bogor Agricultural University (SB-IPB), 2017)
This research attempted to audit the domain of planning and implementation of PT BRL Information System (IS) through the determination of Critical Success Factor (CSF), Key Goal Indicator (KGI), Key Performance Indicator (KPI), to measure maturity level and recommend findings and opportunities to the management for the evaluation and improvement in the maturity level of the Information System of PT BRL using the COBIT framework. From the results of this study, the desired direction of PT BRL management can be identified and a number of recommendations can be formulated to realize the plan. IT governance is an important concept that develops in IT companies and acts as a benchmark for measuring the maturity level of IT organizations (Ayat et al., 2011). Overall, the process of planning and implementation of Information System (IS) in PT BRL has followed the rules according to the COBIT framework and its Maturity Level is at the level of 3 –defined where work procedures have been standardized, documented and communicated through the training process. It has also been mandated that this procedure shall be complied with; however, there is still a deviation of procedures that have not been accommodated in their implementation. There are already standardized and well documented procedures as well as formal training to communicate the procedures and policies set up. Nevertheless, the implementation stage still depends on the individuals whether they are willing to carry out the specified procedure or not. The procedures are still limited to the formalization of the existing practices.Keywords: Auditing, COBIT, CSF, KPI, KGIABSTRAKPenelitian ini berusaha melakukan audit pada domain perencanaan dan implementasi Sistem Informasi (SI) PT BRL melalui penentuan Critical Success Factor (CSF), Key Goal Indicator (KGI), Key Performance Indicator (KPI), mengukur maturity level serta merekomendasikan temuan serta peluang kepada pihak manajemen dalam rangka evaluasi dan peningkatan tingkat kematangan Sistem Informasi (SI) PT BRL menggunakan kerangka kerja COBIT. Dari hasil penelitian ini dapat diketahui arah yang diinginkan manajemen PT BRL serta dapat disusun beberapa rekomendasi untuk dapat mewujudkannya. Tata kelola TI adalah konsep penting yang berkembang di perusahaan TI dan bertindak sebagai patokan untuk mengukur kematangan organisasi TI (Ayat et al. 2011). Secara keseluruhan proses perencanaan dan implementasi Sistem Informasi (SI) di PT BRL sudah mengikuti kaidah-kaidah sesuai dengan kerangka kerja COBIT dan Maturity Level-nya berada pada level: 3 – Defined dimana prosedur kerja telah distandarisasi dan didokumentasikan serta dikomunikasikan melalui proses pelatihan. Telah dimandatkan pula bahwa prosedur ini wajib dipatuhi, namun bagaimanapun juga masih ada deviasi prosedur dalam pelaksanaannya yang belum diakomodasi. Sudah ada prosedur yang memiliki standar dan didokumentasikan dengan baik, sudah ada pelatihan formal untuk mengkomunikasikan prosedur dan kebijakan yang dibuat. Namun pada tahap implementasinya masih tergantung pada individu apakah mau melakukan prosedur yang ditetapkan atau tidak. Prosedur yang dibuat masih terbatas pada bentuk formalisasi dari praktik yang ada.Kata kunci: Audit, COBIT, CSF, KPI, KGI